Pengembangan Model Pengikatan Jaminan Fidusia Dari Objek Bangunan Gedung Untuk Kepastian Hukum Terhadap Eksekusi Jaminan - Poppy Pujiono; Endeh Suhartini; Abraham Yazdi Martin; Sudiman Sihotang (Universitas Djuanda, 2025)
This research aims to analyze the development of a model of fiduciary binding with building objects on other people's land that is just based on contract law and knowing and analyzing legal certainty in credit settlement with building objects on other people's land in bad credit. The method used in this study is the normative juridical law research method. The results showed that the development of a fiduciary binding model with building objects on other people's land that is fair based on contract law can rely on regulations to the Civil Code as the legal basis for its implementation. With the economic value of a kiosk standing on someone else's land, the object can be guaranteed by a fiduciary with a mark of rights, namely, a Deed of Fiduciary Guarantee from a Notary Public and also registered with the Fiduciary Registration Office. Both are using a building rental model, not buying and selling because the building stands on someone else's land rights, namely the DKI Jakarta Provincial Government. The registration also creates legal certainty for the contracting parties, especially if the fiduciary object becomes a credit guarantee at the bank which will remain attached to the executory beslag in it.